Effect of low temperature on fatigue crack propagation rates of DH36 steel and its butt weld. (15th January 2020) - Zhao, Weidong; Feng, Guoqing; Zhang, Ming; Ren, Huilong; Sinsabvarodom, Chana
Abstract: As common marine steel for polar ships, the fatigue crack propagation rates of DH36 steel at low temperature have a crucial influence on the evaluation of the fatigue strength of polar ships. The purpose of this paper is to study the fatigue crack propagation rates of DH36 steel with the different scenarios between the conventional base metal and butt weld specimens at room temperature (RT) and −60 °C. The fatigue crack propagation test and Vickers hardness test of butt weld and base metal were performed. As a result, the fatigue crack propagation test demonstrated a reduced crack propagation rate in both the base metal and the butt weld with a decreasing ambient temperature. For the Vickers hardness, both the welded joint and the base metal at −60 °C presents higher hardness values than RT. Furthermore, the welded joint trends to demonstrates a higher value of Vickers hardness than base metal. Finally, the behavior of fatigue crack propagation in the micro scale between base metal and butt weld at low temperature was described by the fractography. Highlights: The fatigue crack propagation tests were performed at room temperature and −60 °C, The experimental results of fatigue crack propagation test demonstrated a reduced crack propagation rates in the base metal and the butt weld with a decreasing ambient temperature. The Vickers hardness tests were performed at room temperature and −60 °C. The results of Vickers hardness test show, the Vickers hardness of the welded joint and the base metal at −60 °C was higher than that at room temperature, the Vickers hardness of the welded joint was higher than that of the base metal at room temperature and −60 °C. The compliance procedures in the specification (ASTM E466-2015) is still suitable at −60 °C, but the effect of low temperature on the elastic modulus of the material must be considered. The relationship among Vickers hardness, fatigue crack propagation rates and fatigue fracture surface were explained.